2012
DOI: 10.5578/tt.2468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lycopene on the model of oleic acid-induced acute lung injury

Abstract: ÖZET Oleik asit ile oluşturulan akut akciğer hasarı modelinde likopenin etkileri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…The OA-induced ALI rat model was established. 19,20 Control rats were treated with physiological saline at a dosage of 0.1 ml/kg body weight, by intravenous injection; OA group was given OA at a dosage of 0.1 ml/kg body weight, by intravenous injection for 2 h and 6 h, respectively. In OA þ SO 2 group, SO 2 derivatives, sodium sulfite/sodium bisulfite (Na 2 SO 3 /NaHSO 3 ) at a dosage of 0.54 mmol/kg body weight, were freshly dissolved in deionized water and applied by intraperitoneal injection 30 min before OA treatment.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…The OA-induced ALI rat model was established. 19,20 Control rats were treated with physiological saline at a dosage of 0.1 ml/kg body weight, by intravenous injection; OA group was given OA at a dosage of 0.1 ml/kg body weight, by intravenous injection for 2 h and 6 h, respectively. In OA þ SO 2 group, SO 2 derivatives, sodium sulfite/sodium bisulfite (Na 2 SO 3 /NaHSO 3 ) at a dosage of 0.54 mmol/kg body weight, were freshly dissolved in deionized water and applied by intraperitoneal injection 30 min before OA treatment.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Zhang et al (11) reported that intraperitoneal injection of MAT (100 mg/kg) protected against LPS-induced ALI in a mouse model. Türkoğlu et al (15) observed that LY (at 200 times the recommended daily intake in humans) exhibited protective effects in a rat model of oleic acid-induced ALI. The high doses and administration protocols in these studies restricted their clinical usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Lycopene (LY; Fig. 1B) is a member of the carotene family (15). As it has been reported that ALI involves superoxide radicals and inflammatory processes (16,17), it was hypothesized that combined treatment with MAT and LY may protect the lungs from ALI.…”
Section: Introductionmentioning
confidence: 99%
“…As lipopolysaccharide is not the only way to induce acute lung injury, other studies have incorporated alternative methods to study lycopene's effect. A study investigated the effects of Redivio® capsules (lycopene in 10% fluid suspension) against oleic acid (OA)-induced ALI in Wistar rats [48]. Over five weeks, the rats were treated with 100 mg/kg BW/day OA and 20 mg/kg BW/day lycopene.…”
Section: Acute Lung Injurymentioning
confidence: 99%